Influencing Factors of the Development of Village Basketball Association on Hometown Improvement of Sense of Belonging in Guizhou - Yunjing Pan (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Participation in sports plays a vital role in enhancing the social identity of cities in China. This enhancement's mechanisms can differ based on social mentalities and identity conditions. Therefore, it is imperative to bolster the impact of sports participation on residents' social identity in the contemporary era. A productive starting point for this initiative involves enriching the ideological content of physical education curricula. Such an approach can significantly enhance the effectiveness of sports participation in fostering social identity among residents with diverse backgrounds, ultimately contributing to a heightened sense of belonging, particularly in regions such as Guizhou. This study, conducted through an online questionnaire distributed to 373 participants in Guizhou, delves into the correlation between the Village Basketball Association and the hometown improvement of the sense of improvement. The findings underscore that community participation, cultural identity and pride, and sustainable development positively correlate with the hometown's sense of belonging in Guizhou.